2016
DOI: 10.1177/2158244016652925
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Malay and English Research Article Discussions

Abstract: This study investigated the rhetorical organization of Malay and English research article discussions. A move analysis was carried out for the two sets of data of the present study based on a modified version of Peacock's model for the discussion section. For this purpose, a total of 40 research article discussions restricted to empirical studies (20 from each corpus) were randomly selected from journals in the field of education. Results show that Malay discussions are more context dependent while English dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…He found that 100% of the Discussion sections in Law contained 'providing background knowledge', out of which 40.0% involved a restatement of 'aims, methodology, theory and concepts', while 60.0% involved the presentation of claims, generalizations, and research gaps (Tessuto, 2015, p. 19). However, this reference to claims, generalizations and research gaps is not evident in other models (Basturkmen, 2012;Loi et al, 2016;Peacock, 2002;Yang & Allison, 2003), which largely consider background information as consisting of references to the context, theory, objectives and methods of the study being reported. For instance, Basturkmen (2012, p. 137) reported that in Dentistry Discussion sections, 'background information' is referred to "research purposes, theory (and) methodology."…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…He found that 100% of the Discussion sections in Law contained 'providing background knowledge', out of which 40.0% involved a restatement of 'aims, methodology, theory and concepts', while 60.0% involved the presentation of claims, generalizations, and research gaps (Tessuto, 2015, p. 19). However, this reference to claims, generalizations and research gaps is not evident in other models (Basturkmen, 2012;Loi et al, 2016;Peacock, 2002;Yang & Allison, 2003), which largely consider background information as consisting of references to the context, theory, objectives and methods of the study being reported. For instance, Basturkmen (2012, p. 137) reported that in Dentistry Discussion sections, 'background information' is referred to "research purposes, theory (and) methodology."…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the four main sections of the RA, the Discussion section is known to be more difficult for novice scholars (Loi et al, 2016) because writers are expected to go beyond the direct reporting of what have been conducted and found. This means that writers need to structure their Discussion section appropriately to make a powerful "closing argument" (Annesley, 2010(Annesley, , p. 1671 using various information elements, such as objectives, key findings, explanations for the findings, and strengths and/or limitations of their study (Basturkmen & Bitchener, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In another study of research articles in Management, Lim (2008a) reported that recommendations for further research appeared in 95% of the Discussion sections in the discipline, but did not include any information on the recommendations for practical applications or the "implications of the study for professional practice or applied settings" (Basturkmen & Bitchener, 2005) which, in the case of applied disciplines, are understandably important. A more recent study conducted by Loi, Evans, Lim, and Akkakoson (2016), however, was more specific in reporting that implications for the study (focusing on practical contributions and applications) and recommendations for further research appear in 65% and 70% of the educational Discussion sections (in English) respectively. Such different results explain (i) why our findings (to be reported later) can be compared with only the available figures reported in these previous studies, and (ii) why it would be meaningful to look into the degrees of prevalence of each type of recommendation in this study in order to examine how directions for the future are highlighted differently in an applied science discipline such as Forestry.…”
Section: Discipline Applied Linguistics Dentistry Educationmentioning
confidence: 98%
“…If we compare the average degrees of prevalence of these two types of deduction, it can be observed that recommendations for further research appear in nearly all (95%) of the Discussion sections in Management (Lim, 2008a), but only two-thirds of the Discussion sections in both Forestry and Education. To be precise, recommendations for further research are incorporated in about 66.7% of the Discussion sections in Forestry and 65.0% of those in Education (Loi et al, 2016). Such a figure in Vol.…”
Section: Conclusion and Pedagogical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation